2011
DOI: 10.1177/016264341102600202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bridge from Multimedia Cases to Classrooms: Evidence of Transfer

Abstract: This article reports findings from a follow-up study of teacher education students who utilized multimedia cases in coursework in preparation for teaching students with emotional/behavioral disorders. The purpose of the study was to examine the extent to which knowledge, skills, and attitudes gained through multimedia case-based instruction were maintained following coursework with the cases and transferred to discussions of classroom practice. Research subjects included 16 students who agreed to participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Furthermore, despite equal amounts of discussion, the content of the discussion was not equal across the sections, as indicated by differences in overall coverage of problem-finding and problem-solving space, as well as differences in those aspects of the case that students spent most of their time discussing (design solutions vs. project constraints). As noted earlier, novices tend to spend significant time and effort interpreting problem situations/constraints (Fitzgerald et al 2011;Ng and Tan 2006;Perez and Emery 1995;Rowland 1992;Hmelo-Silver et al 2002). Yet they often fail to define the problem adequately and may fail to develop workable solutions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, despite equal amounts of discussion, the content of the discussion was not equal across the sections, as indicated by differences in overall coverage of problem-finding and problem-solving space, as well as differences in those aspects of the case that students spent most of their time discussing (design solutions vs. project constraints). As noted earlier, novices tend to spend significant time and effort interpreting problem situations/constraints (Fitzgerald et al 2011;Ng and Tan 2006;Perez and Emery 1995;Rowland 1992;Hmelo-Silver et al 2002). Yet they often fail to define the problem adequately and may fail to develop workable solutions.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, in this study, this result seems to suggest that students in the NF2 discussion may have been overly concerned about the project constraints and perhaps unable to move forward to consider potential solutions. Findings from previous research (Fitzgerald et al 2011;Kim and Hannafin 2008) suggest that while experts are able to quickly filter through the details of a situation to narrow the problem space and determine key elements (Ertmer et al 2008), novices tend not to do this on their own. As noted by Fitzgerald et al (2011), ''novices expend significant time and effort in interpreting situations, tend to focus on irrelevant information, and fail to identify problems adequately or to develop solutions'' (p. 3).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, given that a case library database is meant to replicate networked memories, the nodes and connections of concept maps potentially could serve as a proxy representation of the desired interconnectedness of indices and memories described by CBR. Prior research has also demonstrated the connection between using concept maps to assess differences in case library design (Fitzgerald et al, 2009(Fitzgerald et al, , 2011.…”
Section: Design and Enactmentmentioning
confidence: 99%
“…While scaffolding may reference a more knowledge peer or instructor, research has also shown technology to be effective in scaffolding student problem-solving. For instance, hypermedia (Saye and Brush 2002), question prompts (Clark et al 2007;Noroozi et al 2013), cases (Boshuizen et al 2012;Fitzgerald et al 2011) have been shown to support student learning on factors such as collaboration, conceptual change, and procedural knowledge.…”
Section: Scaffolding and Self-directed Learningmentioning
confidence: 99%